KEEFEKTIFAN STRATEGI MIND MAPPING TERHADAP PEMAHAMAN KONSEP MATEMATIS MAHASISWA - Nasution, Ulfah Syuhada; Dewi, Muthia; Manurung, Sari Bunga Tiara (Smart Education, 2022)
Abstract: This study is entitled The Effectiveness of Mind Mapping Strategies on Students' Understanding of Mathematical Concepts. This study aims to determine whether there is an Effectiveness of the Mind Mapping Strategy on the Understanding of Students' Mathematical Concepts at STMIK Royal Kisaran in Linear Algebra Courses. The population in this study were all Computer System Students for the 2021/2022 Academic Year. This research is an experimental research involving SK 2A class being an experimental class of 35 students and SK2 B being a control class of 35 students. Based on the results of testing the hypothesis, values and, then this states that there is an Effective Mind Mapping Strategy for Understanding Mathematical Concepts of Students at STMIK Royal Kisaran in Linear Algebra CoursesKeywords: Mind Mapping; Understanding Mathematical ConceptsAbstrak: Penelitian ini berjudul Keefektifan Strategi Mind Mapping Terhadap Pemahaman Konsep Matematis Mahasiswa. Penelitian ini bertujuan untuk mengetahui apakah terdapat Keefektifan Strategi Mind Mapping terhadap Pemahaman konsep Matematis Mahasiswa di STMIK Royal Kisaran pada Mata Kuliah Aljabar Linier. Populasi dalam Penelitian ini adalah Seluruh Peserta didik Sistem Komputer Tahun Ajaran 2021/2022. Penelitian ini merupakan Penelitian Eksperimen yang melibatkan kelas SK 2A menjadi kelas Eksperimen sebanyak 35 mahasiswa dan SK2 B menjadi kelas kontrol sebanyak 35 mahasiswa. Berdasarkan hasil pengujian hipotesis, nilai dan, Maka Hal ini menyatakan bahwa terdapat Keefektifan Strategi Mind Mapping terhadap Pemahaman konsep Matematis Mahasiswa di STMIK Royal Kisaran pada Mata Kuliah Aljabar Linier.Kata kunci: Mind Mapping;Pemahaman Konsep Matematis